Standardized nursing and clinical efficacy of OxyContin in reducing oral mucosal pain in patients with nasopharyngeal carcinoma: A randomized, double-blind, placebo-controlled study protocol. Issue 49 (4th December 2020) - Sun, Nina; Li, Yunxia; Nie, Peihua
Abstract: Background: Pain caused by oral mucositis (OM) is the main problem in the process of concurrent chemoradiotherapy for the nasopharyngeal carcinoma (NPC). This protocol aims to explore the standardized nursing and therapeutic effect of OxyContin on OM pain in the patients with NPC undergoing the concurrent chemoradiotherapy. Methods: The experiment is a randomized clinical research, which was granted through the Research Ethics Committee of Shandong Provincial Third Hospital (No.20200802097). In this research, 90 NPC patients with OM induced by chemotherapy are enrolled, and the score of visual analogue >5 and the grade of OM >1 are evaluated. Patients with known allergy to OxyContin, the opioid abuse history, or major organ dysfunction, for instance, hepatic insufficiency, renal failure, and respiratory and heart failure, as well as a series of severe mental illness are excluded from our research. Patients in study groups receive standardized nursing and oral OxyContin. Patients in control groups only receive oral OxyContin. The analgesic effect could be assessed with the comparison of the visual analogue scale after and before the treatment. Safety evaluations contain the assessment of the vital signs, laboratory tests, as well as adverse events. The Karnofsky performance status standards of the International Cancer Control Union is utilized to evaluate the quality of life. Results: The comparison of outcomes after taking OxyContin in both groups will be shown in Table 1 . Conclusion: The combination of OxyContin and standardized nursing care appears to improve the analgesic efficacy and life quality in NPC patients. Trial registration: We registered this protocol in Research Registry (researchregistry6098).